FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI - Ariani, Ni Komang Ayu; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
The purpose of this study was to determine the factors that affect the company's capital structure on property & real estate listed on the Indonesia Stock Exchange 2013-2015 period. This study uses a variable profitability, asset structure, growth opportunities, non-debt tax shield, the size of the company as an independent variable and capital structure as the dependent variable. This study uses census entire property & real estate companies listed on the Indonesia Stock Exchange 2013-2015 period, namely a number of 43 companies. Data analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that profitability, non-debt tax shield, and the size of the company partially has a negative and significant impact on the capital structure, while the structure of assets and growth opportunities Partial have a positive and significant impact on the capital structure.
Keywords: capital structure, profitability, growth opportunities, non-debt tax shield, size .